Role of monocytes/macrophages in renin-angiotensin system-induced hypertension and end organ damage - Barhoumi, Tlili; Todryk, Stephen (Frontiers in Physiology, 2023)
The renin-angiotensin system (RAS) is a central modulator of cardiovascular physiology.Angiotensin II receptor blockers (ARBs) and Angiotensin-converting enzyme (ACE) inhibitors are the gold standard treatment for hypertension. Recently, several studies highlighted the crucial role of immune system in hypertension. Angiotensin-II-induced hypertension is associated with low grade inflammation characterized by innate and adaptive immune system dysfunction.Throughout the progression of hypertension, monocyte/macrophage cells appear to have a crucial role in vascular inflammation and interaction with the arterial wall. Since myelomonocytic cells potentially play a key role in angiotensin-II-induced hypertension and organ damage, pharmacological targeting of RAS components in monocyte/macrophages may possibly present an innovative strategy for treatment of hypertension and related pathology.